Synagoge = Synagōgē lexeōn chrēsimōn : texts of the original version and of MS. B - Cunningham, Ian Campbell (Sammlung griechischer und lateinischer Grammatiker, 2003)
The ""Synagoge"" (Gk: collection of useful word explanations) is one of the most important lexicographical sources from early Byzantine times. The anonymous author quotes extracts from the works of ancient authors which have not been preserved elsewhere and gives details of customs and myths from the epoch. At the same time, he presents his own age and provides a rich source of information on education and scholarship. The present edition combines all the available manus.